COMPARATIVE ASSESSMENT OF TERMS FATTENING OF STURGEONS FISH IN THE WATERS OF THE CASPIAN STATES - A. F. Sokolsky; A. A. Polyaninova; A. A. Molodtsova; G. M. Abdurakhmanov; E. A. Sokolskaya (Юг России: экология, развитие, 2014)
The article presents materials on the terms of the feeding area of sturgeon in the waters of all the Caspian States.